Proposta de um modelo de chicana para lagoas facultativas utilizando ferramentas de fluidodinâmica computacional - Garcia, Leandro Conti (2019)
Social development has always been linked to the search for sanitation, because it is necessary for the promotion of public health. The best known and most widely used domestic sewage treatment method in Brazil is the stabilization pond system, which is efficient in removing organic pollutants, but can present operational problems such as sediment accumulation, dead zones and short circuit zones, that happen due to the lack of maintenance or operational errors, negatively influencing the treatment efficiency. The use of baffles is a way of mitigating these problems, making the objective of this work the proposition of an alternative model of mobile and floating baffles through a stabilization pond study. The study development began with the collection of bathymetric data in a stabilization pond in the municipality of Campo Mourão, the creation of a three-dimensional sediment layer model in the lagoon bed, fluid hydrodynamic behavior evaluation, baffle model development and the hydrodynamic behavior evaluation of four baffle layout configurations (scenarios). In scenario one, the baffles would be fixed to the sides and center of the lagoon, parallel to the entry and exit session. Scenarios two and three would have baffles fixed only to the sides of the lagoon, still parallel to the inlet and outlet sessions, and scenario four would have baffles parallel to the flow direction, conditioning the formation of the piston flow. Hydrodynamic evaluation was performed by computational fluid dynamics. From the development of the methodology, the main operational problems and its areas of occurrence were identified, thus conditioning the configurations choice for the baffles arrangement. Its use allowed the mitigation of major problems, such as sediment accumulation, and it was able to increase flow velocity in all scenarios, as well as approximate the real hydraulic detention time to the operation. According to the obtained data, and the simulations visual analysis, it is possible to affirm that the configuration of baffles evaluated in the scenario four would be more appropriate to the mitigation of the operational problems found in the studied pond, since this arrangement conditions the piston flow, which provides less sediment accumulation as well as lower dead zones and short circuit zones development in the bed. It was concluded that the installation of baffles is able to mitigate the stabilization ponds operational problems by directing the flow. Likewise, it was possible to observe the need for continuous studies that allow the improvement of effluent treatment systems.